Chromium coating zirconium alloy cladding tube sample for EBSD (electron back-scattered diffraction) test as well as preparation method and application of chromium coating zirconium alloy cladding tube sample
The preparation of chromium-coated zirconium alloy shelled tube samples through cutting, inlay, grinding, polishing and pickling steps, solving the problem that the sample surface quality is difficult to meet the EBSD testing requirements, and achieving efficient sample preparation and accurate microstructure characterization.
Patent Information
- Application Number
- CN202411960392.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to meet the surface quality requirements of chrome-coated zirconium alloy shelled tube samples, especially in EBSD tests, the surface of the sample needs to be flat, clean and strainless.
The chromium-coated zirconium alloy shelled tube samples were prepared by cutting, inlay, grinding, mechanical polishing, fine polishing, pickling and cleaning. Through step-by-step polishing and pickling treatment, ensure that the sample surface meets the requirements of EBSD testing.
The EBSD calibration rate of chrome-coated zirconium alloy clad tube samples was improved to 96%, so that the sample characterization results can truly reflect their microstructure information, providing strong support for the research and development of fault-tolerant fuel clad materials for nuclear reactor accidents.
Smart Images

Figure CN119780134A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of zirconium alloy material processing, and in particular to a chromium-coated zirconium alloy cladding tube sample for EBSD testing, and a preparation method and application thereof. Background Art
[0002] The chromium coating has a small thermal neutron absorption cross section, excellent oxidation resistance and good matching with zirconium alloy, making the chromium-coated zirconium alloy one of the most likely accident-tolerant fuel cladding materials for industrial application. Before the chromium-coated zirconium alloy cladding tube is put into service, its comprehensive performance needs to be fully studied and evaluated, including high-temperature steam oxidation, high-temperature and high-pressure water corrosion and hydrogen absorption behavior, irradiation damage, internal pressure fatigue / creep, and interaction between cladding and pellets. However, the above performance is closely related to the microstructure of the chromium-coated zirconium alloy cladding tube, such as grain morphology, size and orientation.
[0003] Electron backscatter diffraction (EBSD) technology is a commonly used analytical method to determine the crystal structure and orientation information of materials, but it has extremely high requirements for the surface quality of chromium-coated zirconium alloy cladding tube samples, requiring the sample surface to be flat, clean, and free of strain layers, which poses a challenge to the preparation of chromium-coated zirconium alloy cladding tube samples. Generally speaking, zirconium alloy has a close-packed hexagonal structure and a low hardness, so it is suitable to use the pickling method to obtain a bright surface for EBSD testing; while chromium metal has a body-centered cubic structure and a higher hardness than zirconium alloy, so it is suitable to use grinding and polishing methods to prepare EBSD samples. It can be seen that the preparation methods of chromium coating and zirconium alloy samples are different. Therefore, a single grinding and polishing or pickling method is difficult to meet the surface quality requirements of chromium-coated zirconium alloy cladding tube samples, and other innovative preparation methods are required.
[0004] Patent publication number CN117646162A discloses a surface treatment method for zirconium alloy cladding tubes for coating, which includes pickling to remove particles and debris on the surface, and polishing with a sandless pure cork sand belt to reduce surface scratches, particle accumulation, and tear marks, which are then combined with the coating to avoid cracking and shedding of the coating during service in the reactor, thereby preventing the zirconium alloy cladding tubes from failing in wind protection. However, the obtained zirconium alloy cladding tubes still need to be prepared as samples before EBSD testing. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a chromium-coated zirconium alloy cladding tube sample for EBSD testing and its preparation method and application, so that the prepared chromium-coated zirconium alloy cladding tube sample meets the EBSD test requirements, and its characterization results can truly reflect the microstructure information of the chromium-coated zirconium alloy cladding tube, providing strong support for the research and development of nuclear reactor accident-tolerant fuel cladding materials.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing a chromium-coated zirconium alloy cladding tube sample for EBSD testing, comprising the following steps:
[0008] S1. Cutting: cutting and cleaning the chromium-coated zirconium alloy cladding tube;
[0009] S2, inlaying: inlaying and fixing the chromium-coated zirconium alloy cladding tube cut in step S1;
[0010] S3, grinding: grinding the surface of the chromium-coated zirconium alloy cladding tube after inlaying in step S2 until the surface is smooth and free of burrs;
[0011] S4, mechanical polishing: mechanically polishing the chromium-coated zirconium alloy cladding tube after grinding in step S3 until there are no scratches on the surface;
[0012] S5, fine polishing: fine polishing the chromium-coated zirconium alloy cladding tube after mechanical polishing in step S4;
[0013] S6, pickling: using acid to wipe the surface of the chromium-coated zirconium alloy cladding tube finely polished in step S5;
[0014] S7, cleaning: the chromium-coated zirconium alloy cladding tube after pickling in step S6 is rinsed with water, ultrasonically cleaned with ethanol, and blown dry in sequence to obtain a chromium-coated zirconium alloy cladding tube sample, and the preparation is completed.
[0015] Furthermore, the chromium-coated zirconium alloy cladding tube used in step S1 includes a zirconium alloy cladding tube and a chromium coating located on its outer surface, wherein the chromium coating is prepared by processes such as magnetron sputtering or multi-arc ion plating, the outer diameter of the zirconium alloy cladding tube is 8 to 10 mm, the wall thickness is 0.4 to 0.6 mm, and the thickness of the chromium coating is 10 to 20 μm.
[0016] Furthermore, the element composition of the zirconium alloy cladding tube includes zirconium, iron, tin, niobium, chromium, etc., wherein the mass fraction of zirconium is more than 95%, and the sum of the mass fractions of trace alloying elements such as iron, tin, niobium, chromium, etc. is less than 5%.
[0017] Furthermore, in step S1, the chromium-coated zirconium alloy cladding tube is cut into a tubular sample with a length of 0.5 to 1 cm, and the cut surface is perpendicular to the axial direction; the cut chromium-coated zirconium alloy cladding tube is rinsed and ultrasonically cleaned with water and ethanol.
[0018] Furthermore, in step S1, the cutting method is wire cutting, grinding wheel cutting, wire saw cutting, so that the cut end surface is flat.
[0019] Furthermore, in step S2, the chromium-coated zirconium alloy cladding tube cut in step S1 is hot-mounted or cold-mounted with resin, so that the resin is tightly bonded to the surface of the chromium coating after solidification.
[0020] The specific parameters of the hot mounting are: temperature of 16-200°C, pressure of 20-30MPa, and time of 2-8min;
[0021] The specific parameters of the cold mounting are: normal temperature and normal pressure, and the cold mounting resin curing time is 8 to 16 hours.
[0022] Furthermore, the hot mounting resin includes phenolic resin for electron microscopy.
[0023] The cold mounting resin is a mixture of epoxy resin and cold mounting curing agent, which are mixed in a weight ratio of 25:1-5 or a volume ratio of 15:1-5.
[0024] Further, in step S3, the surface of the chromium-coated zirconium alloy cladding tube after inlaying in step S2 is grinded using silicon carbide sandpapers of 800 mesh, 1000 mesh, 1500 mesh, 2000 mesh and 3000 mesh in sequence until the surface is flat and burr-free, and uniform scratches in a uniform direction are observed with the naked eye.
[0025] Furthermore, in step S4, the chromium-coated zirconium alloy cladding tube ground in step S3 is mechanically polished using 2-3 μm and 0.5-1.5 μm diamond polishing pastes in sequence, with the mechanical polishing speed being 250-300 rpm, until there are no scratches on the surface.
[0026] Furthermore, in step S5, the chromium-coated zirconium alloy cladding tube after mechanical polishing in step S4 is finely polished using a silicon oxide suspension with a particle size of 30 to 50 nm. The fine polishing speed is 100 to 200 rpm and the fine polishing time is 10 to 120 min.
[0027] Further, in step S6, the acid solution is a mixed acid of lactic acid, nitric acid and hydrofluoric acid, and the volume ratio of the three is 4 to 10:4 to 10:1;
[0028] The concentration of lactic acid is 85.5% to 92.0%, the concentration of nitric acid is 65.0% to 68.0%, and the concentration of hydrofluoric acid is not less than 40.0%;
[0029] The time for wiping the surface of the chromium-coated zirconium alloy cladding tube finely polished in step S5 with acid solution is 15 to 20 seconds.
[0030] The second technical solution of the present invention is to provide a chromium-coated zirconium alloy cladding tube sample for EBSD testing, which is prepared by using the preparation method of a chromium-coated zirconium alloy cladding tube sample.
[0031] The third technical solution of the present invention is to provide an application of a chromium-coated zirconium alloy cladding tube sample for EBSD testing in EBSD testing.
[0032] Compared with the prior art, the present invention has the following advantages:
[0033] (1) The chromium-coated zirconium alloy cladding tube sample prepared by the preparation method of the present invention has an EBSD calibration rate of up to 96%, while the current conventional EBSD calibration rate is about 85%. The prepared chromium-coated zirconium alloy cladding tube sample meets the EBSD test requirements, and its characterization results can truly reflect the microstructure information of the chromium-coated zirconium alloy cladding tube, providing strong support for the research and development of nuclear reactor accident-tolerant fuel cladding materials.
[0034] (2) The present invention cuts, inlays, grinds, mechanically polishes, finely polishes, pickles, and cleans the chromium-coated zirconium alloy cladding tube. The zirconium alloy has a close-packed hexagonal structure. During the grinding and polishing process, due to the relatively close atomic arrangement of this structure, the force of the abrasive particles on the surface of the zirconium alloy will cause the surface atomic layer to displace and form a strain layer. For zirconium alloy, by selecting a suitable acid solution, the raised part of the zirconium alloy surface can be corroded first, thereby achieving the effect of a flat surface. At the same time, the pickling process can remove the oxide layer and other impurities on the surface, making the surface cleaner. At the same time, since there is no mechanical force, the strain layer will not be introduced like grinding and polishing, which can better meet the EBSD requirement that the sample surface has no strain layer. Chromium metal is a body-centered cubic structure, the bonding force between its atoms is strong, and the hardness is higher than that of zirconium alloy. During the grinding and polishing process, the chromium coating can withstand the grinding action of the abrasive. By gradually using finer abrasives, the surface processing marks and roughness can be effectively removed to obtain a relatively flat surface. The chemical activity of chromium in certain acid solutions is relatively low, and simple pickling may not be able to effectively remove impurities and roughness on the surface of the chromium coating. The chromium coating may form a passivation film during the pickling process. Although this film can play a protective role to a certain extent, it will affect the interaction between the electron beam and the sample surface for EBSD testing, resulting in inaccurate crystal orientation information. First, grind and polish the chromium coating, take advantage of its hardness, and use appropriate abrasives and processes to remove most of the surface roughness and processing marks; then pickle and treat the small amount of impurities remaining on the surface of the chromium coating and the zirconium alloy surface after grinding and polishing, which can more comprehensively improve the surface quality of the sample. Precisely controlling parameters during grinding and polishing can avoid excessive damage to the chromium coating; choosing appropriate acid and conditions during pickling can protect the chromium coating from excessive corrosion, while allowing the acid to effectively clean the zirconium alloy surface and residual impurities in the chromium coating, ensuring that the surface quality of the entire sample meets the EBSD detection requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1This is a photo of the appearance of the chromium-coated zirconium alloy cladding tube sample prepared in Example 1;
[0036] Figure 2 The cross-sectional EBSD characterization results of the chromium-coated zirconium alloy cladding tube sample prepared in Example 1, (a) Kikuchi pattern contrast map + grain boundary map, (b) grain orientation distribution map along the tangential direction of the cladding tube, (c) crystal orientation pole figures of zirconium and chromium, (d) grain orientation distribution map along the radial direction of the cladding tube, (e) grain orientation distribution map along the axial direction of the cladding tube, (f) axial, radial and tangential schematic diagrams of the chromium-coated zirconium alloy;
[0037] Figure 3 The cross-sectional EBSD characterization results of the chromium-coated zirconium alloy cladding tube sample prepared in Example 2, (a) Kikuchi pattern contrast map + grain boundary map, (b) grain orientation distribution map along the tangential direction of the cladding tube, (c) crystal orientation pole figures of zirconium and chromium, (d) grain orientation distribution map along the radial direction of the cladding tube, (e) grain orientation distribution map along the axial direction of the cladding tube, (f) axial, radial and tangential schematic diagrams of the chromium-coated zirconium alloy;
[0038] Figure 4 The cross-sectional EBSD characterization results of the chromium-coated zirconium alloy cladding tube sample prepared in Example 3, (a) Kikuchi pattern contrast map + grain boundary map, (b) grain orientation distribution map along the tangential direction of the cladding tube, (c) crystal orientation pole figures of zirconium and chromium, (d) grain orientation distribution map along the radial direction of the cladding tube, (e) grain orientation distribution map along the axial direction of the cladding tube, (f) axial, radial and tangential schematic diagrams of the chromium-coated zirconium alloy;
[0039] Figure 5 The cross-sectional EBSD characterization results of the chromium-coated zirconium alloy cladding tube sample prepared in Comparative Example 1, (a) Kikuchi pattern contrast map + grain boundary map, (b) grain orientation distribution map along the tangential direction of the cladding tube, (c) crystal orientation pole figures of zirconium and chromium, (d) grain orientation distribution map along the radial direction of the cladding tube, (e) grain orientation distribution map along the axial direction of the cladding tube, (f) axial, radial and tangential schematic diagrams of the chromium-coated zirconium alloy;
[0040] Figure 6 The cross-sectional EBSD characterization results of the chromium-coated zirconium alloy cladding tube sample prepared in Comparative Example 2, (a) Kikuchi pattern contrast map + grain boundary map, (b) grain orientation distribution map along the tangential direction of the cladding tube, (c) crystal orientation pole figures of zirconium and chromium, (d) grain orientation distribution map along the radial direction of the cladding tube, (e) grain orientation distribution map along the axial direction of the cladding tube, (f) axial, radial and tangential schematic diagrams of the chromium-coated zirconium alloy;
[0041] Figure 7The cross-sectional EBSD characterization results of the chromium-coated zirconium alloy cladding tube sample prepared in Comparative Example 3, (a) Kikuchi pattern contrast map + grain boundary map, (b) grain orientation distribution map along the tangential direction of the cladding tube, (c) crystal orientation pole figures of zirconium and chromium, (d) grain orientation distribution map along the radial direction of the cladding tube, (e) grain orientation distribution map along the axial direction of the cladding tube, (f) axial, radial and tangential schematic diagrams of the chromium-coated zirconium alloy. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0043] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.
[0044] In the following embodiments, the outer diameter of the zirconium alloy cladding tube in the chromium-coated zirconium alloy cladding tube is 9.5 mm, the wall thickness is 0.57 mm, and the element composition includes zirconium, iron, tin, niobium, chromium, etc., wherein the mass fraction of zirconium is more than 95%, and the sum of the mass fractions of trace alloy elements such as iron, tin, niobium, chromium, etc. is less than 5%; the chromium coating is located on the outer surface of the zirconium alloy cladding tube, has a thickness of 15 μm, and is composed of pure chromium metal.
[0045] The hot mounting resin used was PolyFast carbon-containing conductive phenolic resin for scanning electron microscopy, EpoFix epoxy resin and cold mounting curing agent mixed in a weight ratio of 25:2, all of which were purchased from Struers. Diamond polishing paste was from Zhengzhou Abrasives and Grinding Research Institute Co., Ltd., silicon oxide suspension was from Buehler, and lactic acid and other acids were from Sinopharm Chemical Reagent Co., Ltd.
[0046] Example 1
[0047] A method for preparing a chromium-coated zirconium alloy cladding tube sample for EBSD testing comprises the following steps:
[0048] S1. Cutting: Use a precision cutting machine to cut a 0.5 cm long tubular sample from the chromium-coated zirconium alloy cladding tube with a grinding wheel. The cut end surface is flat and the cut surface is perpendicular to the axial direction. After the cutting is completed, the cut tubular sample is immediately ultrasonically cleaned with water to remove the oil stains remaining on the sample surface during the cutting process.
[0049] S2, Mounting: Place the tubular sample cut and cleaned in step S1 into the hot mounting machine mold, adjust the sample position so that it is in the center of the mold, weigh 15 ml of hot mounting resin, pour it into the mounting machine mold, then heat it to 180°C and pressurize it to 25 MPa for hot mounting, and the mounting time is 3.5 minutes. After the mounted sample is completely cooled, take it out of the hot mounting machine mold, and the hot mounting resin will be tightly bonded to the surface of the chromium coating after solidification.
[0050] S3, grinding: Use 800 mesh, 1000 mesh, 1500 mesh, 2000 mesh and 3000 mesh silicon carbide sandpaper to grind the sample mounted in step S2 in turn to remove the burrs generated by the cutting machine until the surface of the sample is flat and uniform scratches in a uniform direction are observed with the naked eye.
[0051] S4, mechanical polishing: polish the sample after grinding in step S3 using diamond polishing pastes with a particle size of 2.5 μm and 1 μm respectively, with the polishing machine speed set to 300 rpm until the scratches generated by the grinding process are eliminated.
[0052] S5. Fine polishing: Use a silicon oxide suspension with a particle size of 40 nm to fine polish the sample after mechanical polishing in step S4. The polishing machine speed is set to 150 rpm and the polishing time is 20 min.
[0053] S6, pickling: pickling the sample after mechanical polishing in step S5, and constantly wipe the sample surface with cotton dipped in acid solution for 18 seconds during the pickling process. The acid solution is a mixed acid of lactic acid, nitric acid, and hydrofluoric acid, and the volume ratio of the three is 5.6:5.6:1; the concentration of lactic acid is 90%, the concentration of nitric acid is 65%, and the concentration of hydrofluoric acid is 50.0%. During the preparation of the mixed acid, the operator needs to wear protective gloves, goggles and other protective equipment, and operate in a fume hood to prevent the acid from causing harm to the human body.
[0054] S7, cleaning: After the pickling is completed, immediately place the sample after the pickling in step S6 under running deionized water for cleaning, and thoroughly rinse the acid on the surface of the sample to ensure that the pH value of the sample surface is close to neutral. Then put the sample into a beaker filled with anhydrous ethanol for ultrasonic cleaning. After the ultrasonic cleaning is completed, take out the sample and use a cold air blower to dry the surface of the sample, and finally obtain a chromium-coated zirconium alloy cladding tube sample, such as Figure 1 As shown. During the rinsing process, the water flow is kept stable and uniform to avoid excessive water flow causing impact on the specimen. During the drying process, the hair dryer maintains a stable wind force and direction to ensure that the surface of the specimen is evenly dried to avoid local overheating or incomplete drying.
[0055] The prepared chromium-coated zirconium alloy cladding tube sample was subjected to EBSD test. Figure 2The EBSD characterization results of the cross section of the chromium-coated zirconium alloy cladding tube sample prepared in Example 1. The zirconium alloy substrate is an equiaxed crystal structure, while the chromium coating is an elongated columnar crystal structure. Both the chromium coating and the zirconium alloy substrate have a certain degree of preferred orientation. The EBSD calibration rate of this example is 96%, which is obtained by analyzing the AZtecCrystal software of Oxford Instruments.
[0056] Example 2
[0057] Compared with Example 1, most of them are the same, except that the pickling time in step S6 is adjusted to 15 seconds. Figure 3 This is the EBSD characterization result of the cross section of the chromium-coated zirconium alloy cladding tube sample prepared in Example 2. The EBSD calibration rate of this example is 87%, which is obtained by analyzing with the AZtecCrystal software of Oxford Instruments.
[0058] Example 3
[0059] Compared with Example 1, most of them are the same, except that the pickling time in step S6 is adjusted to 20 seconds. Figure 4 This is the EBSD characterization result of the cross section of the chromium-coated zirconium alloy cladding tube sample prepared in Example 3. The EBSD calibration rate of this example is 96%, which is obtained by analyzing with the AZtecCrystal software of Oxford Instruments.
[0060] Example 4
[0061] Compared with Example 1, most of them are the same, except for step S2:
[0062] Place the tubular sample cut and cleaned in step S1 into the hot mounting machine mold, adjust the sample position so that it is in the center of the mold, weigh 15 ml of cold mounting resin, pour them into the mounting machine mold, and perform cold mounting at room temperature and pressure for 12 hours. After mounting, take it out of the mounting machine mold, and the cold mounting resin will be tightly bonded to the chromium coating surface after solidification.
[0063] Comparative Example 1
[0064] Compared with Example 1, most of the steps are the same, except that the pickling time in step S6 is adjusted to 22 seconds. Figure 5 This is the EBSD characterization result of the cross section of the chromium-coated zirconium alloy cladding tube sample prepared in Comparative Example 1. The EBSD calibration rate of this example is 81%, which is obtained by analyzing with the AZtecCrystal software of Oxford Instruments.
[0065] Comparative Example 2
[0066] Compared with Example 1, most of the steps are the same, except that the pickling in step S6 is omitted and the chromium-coated zirconium alloy cladding tube is directly cleaned after fine polishing. Figure 6 This is the EBSD characterization result of the cross section of the chromium-coated zirconium alloy cladding tube sample prepared in Comparative Example 2. The EBSD calibration rate of this example is 38%, which is obtained by analyzing with the AZtecCrystal software of Oxford Instruments.
[0067] Comparative Example 3
[0068] Compared with Example 1, most of the steps are the same, except that the fine polishing in step S5 is omitted and the chromium-coated zirconium alloy cladding tube is directly pickled after mechanical polishing. Figure 7 This is the EBSD characterization result of the cross section of the chromium-coated zirconium alloy cladding tube sample prepared in Comparative Example 3. The EBSD calibration rate of this example is 75%, which is obtained by analyzing with the AZtecCrystal software of Oxford Instruments.
[0069] In summary, the chromium-coated zirconium alloy cladding tube sample prepared by the preparation method of the present invention meets the EBSD test requirements, and its EBSD calibration rate is high, so that its characterization results can truly reflect the microstructure information of the chromium-coated zirconium alloy cladding tube, providing strong support for the research and development of nuclear reactor accident-tolerant fuel cladding materials.
[0070] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a chromium-coated zirconium alloy cladding tube sample for EBSD testing, characterized in that: The following steps are involved: S1. Cutting: cutting and cleaning the chromium-coated zirconium alloy cladding tube; S2, inlaying: inlaying and fixing the chromium-coated zirconium alloy cladding tube cut in step S1; S3, grinding: grinding the surface of the chromium-coated zirconium alloy cladding tube after inlaying in step S2 until the surface is smooth and free of burrs; S4, mechanical polishing: mechanically polishing the chromium-coated zirconium alloy cladding tube after grinding in step S3 until there are no scratches on the surface; S5, fine polishing: fine polishing the chromium-coated zirconium alloy cladding tube after mechanical polishing in step S4; S6, pickling: using acid to wipe the surface of the chromium-coated zirconium alloy cladding tube finely polished in step S5; S7, cleaning: the chromium-coated zirconium alloy cladding tube after pickling in step S6 is rinsed with water, ultrasonically cleaned with ethanol, and blown dry in sequence to obtain a chromium-coated zirconium alloy cladding tube sample, and the preparation is completed.
2. The method for preparing a chromium-coated zirconium alloy cladding tube sample for EBSD testing according to claim 1, characterized in that: In step S1, the chromium-coated zirconium alloy cladding tube is cut into a tubular sample with a length of 0.5 to 1 cm, and the cutting surface is perpendicular to the axial direction; the cut chromium-coated zirconium alloy cladding tube is rinsed and ultrasonically cleaned with water and ethanol in turn.
3. The method for preparing a chromium-coated zirconium alloy cladding tube sample for EBSD testing according to claim 1, characterized in that: In step S2, the chromium-coated zirconium alloy cladding tube cut in step S1 is hot-mounted or cold-mounted with resin.
4. The method for preparing a chromium-coated zirconium alloy cladding tube sample for EBSD testing according to claim 3, characterized in that: The resin includes hot mounting resin and cold mounting resin; The specific parameters of the hot mounting are: temperature of 16-200°C, pressure of 20-30MPa, and time of 2-8min; The specific parameters of the cold mounting are: normal temperature and normal pressure, and the cold mounting resin curing time is 8 to 16 hours.
5. The method for preparing a chromium-coated zirconium alloy cladding tube sample for EBSD testing according to claim 1, characterized in that: In step S3, the surface of the chromium-coated zirconium alloy cladding tube after inlaying in step S2 is grinded using silicon carbide sandpapers of 800 mesh, 1000 mesh, 1500 mesh, 2000 mesh and 3000 mesh in sequence until the surface is flat and burr-free, and uniform scratches in a uniform direction are observed with the naked eye.
6. The method for preparing a chromium-coated zirconium alloy cladding tube sample for EBSD testing according to claim 1, characterized in that: In step S4, the chromium-coated zirconium alloy cladding tube ground in step S3 is mechanically polished using 2-3 μm and 0.5-1.5 μm diamond polishing pastes in sequence, with the rotation speed of the mechanical polishing being 250-300 rpm, until there are no scratches on the surface.
7. The method for preparing a chromium-coated zirconium alloy cladding tube sample for EBSD testing according to claim 1, characterized in that: In step S5, the chromium-coated zirconium alloy cladding tube after mechanical polishing in step S4 is finely polished with a silicon oxide suspension having a particle size of 30 to 50 nm. The fine polishing speed is 100 to 200 rpm and the fine polishing time is 10 to 120 min.
8. The method for preparing a chromium-coated zirconium alloy cladding tube sample for EBSD testing according to claim 1, characterized in that: In step S6, the acid solution is a mixed acid of lactic acid, nitric acid and hydrofluoric acid, and the volume ratio of the three is 4-10:4-10:1; The concentration of lactic acid is 85.5% to 92.0%, the concentration of nitric acid is 65.0% to 68.0%, and the concentration of hydrofluoric acid is not less than 40.0%; The time for wiping the surface of the chromium-coated zirconium alloy cladding tube finely polished in step S5 with acid solution is 15 to 20 seconds.
9. A chromium-coated zirconium alloy cladding tube sample for EBSD testing, prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the chromium-coated zirconium alloy cladding tube sample for EBSD testing as claimed in claim 9 in EBSD testing.
Citation Information
Patent Citations
Surface treatment method of zirconium alloy cladding tube for coating
CN117646162A
Cited By
Annular compression detection method for zirconium alloy cladding tube
CN121324117A